TRANSFORMASI VIRTUAL OFFICE: ANALISIS KESIAPAN SISWA JURUSAN MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS DALAM MENGHADAPI BUDAYA KERJA REMOTE - Tien Karyanti; Yayan Diansyah (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
The transformation of conventional office systems into virtual office environments has created new competency demands for vocational school graduates, particularly students of Office Management. This study aimed to analyze the readiness of students of SMKS Teknologi, Office Management Department, in facing remote work culture through the implementation of virtual office simulation learning. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design involving grade XII students divided into an experimental group and a control group. Data were collected through a readiness questionnaire covering digital literacy, online communication, time management, work discipline, collaboration skills, and technological adaptability. The results showed that the average pretest score of the experimental group was 64.28, which increased to 84.67 in the posttest, indicating an improvement of 20.39 points or 31.72%. Meanwhile, the control group increased from an average score of 63.91 to 71.35, with a gain of 7.44 points or 11.64%. Statistical testing revealed a significant difference between the two groups (p < 0.05), indicating that virtual office simulation learning had a positive effect on students’ readiness to face remote work culture. The most improved aspects included digital communication, collaboration competence, and adaptation to work technology. Therefore, integrating virtual office-based learning into vocational curricula is recommended to enhance graduate competitiveness in the digital workplace era.